Self-assembly of three-dimensional CdS nanosphere/graphene networks for efficient photocatalytic hydrogen evolution - Wang, Zhijian (2020)
In this work, we report the construction of three-dimensional (3D) CdS nanosphere/graphene networks by a one-step hydrothermal self-assembly route. The 3D graphene networks not only enhance the light scattering, thanks to the interconnected 3D architecture, but also improve the crystallinity of deposited CdS nanospheres, and at the same time provide a direct electron pathway to quickly separate the photogenerated electron-hole pairs from CdS, which thus dramatically improve the photocatalytic activity. The optimized 3D CdS nanosphere/graphene networks with 2 wt% of graphene could produce molecular hydrogen at a rate of 2310 µmol gcatalyst−1 h−1 under visible-light illumination (λ > 400 nm).